PENGARUH INFORMASI KEUANGAN DAN INFORMASI NON KEUANGAN TERHADAP INITIAL RETURN DI BURSA EFEK INDONESIA - Zainuddin; Yustiana Djaelani; Muliati (Accounting Profession Journal (APAJI), 2022)
The purpose of this study was to analyze the effect of financial and non-financial information on initial returns on the Indonesia Stock Exchange. Financial information in this study is measured by the variables of earnings per share, debt to equity ratio, return on assets, the proportion of old shareholder ownership, and price earning ratio. Non-financial information is measured by variables of auditor reputation, underwriter reputation, and company age. The data collection method used purposive sampling. The number of research samples is 52 companies that experience underpricing when conducting initial public offerings listed on the Indonesia Stock Exchange in 2015-2018. The analytical tool used is multiple linear regression analysis using SPSS 25 analysis tool. The results show that earnings per share, return on assets, the proportion of old shareholder ownership, underwriter reputation, and company age have a significant effect on initial return. Meanwhile, debt to equity ratio, price earning ratio, and auditor reputation have no effect on initial return.